(untitled) (JSSE - Journal of Science & Sustainable Engineering, 2024)
The catalytic photodegradation of organic pollutants offers an eco-friendly alternative to improving water quality by reducing the use of strong oxidants. This method is particularly promising in dealing with emerging pollutants that are not completely removed using only the traditional methodologies. However, limitations of the main photocatalysts used such as high bandgap value and electronic recombination are a challenge to face when trying to upscale applications. In this study, photocatalytic heterostructures were synthesized using TiO2 P25, carbon quantum dots (CQDs), and silver (Ag) to enhance photocatalytic performance and overcome these challenges. The results demonstrated significant improvements in photodegradation efficiency, with an 827% increase for the catalyst containing only CQDs and a 400% increase for the heterostructures containing both CQDs and Ag. These enhancements are attributed to the synergy of the ballistic electronic transferer properties and the diminished availability of recombination sites of the semiconductor which enables the generation of oxidative radicals.